Islamic Social Reporting Disclosure on Manufacturing Companies in the Jakarta Islamic Index and Bursa Malaysia 2016-2020 - A. Jajang W. Mahri; Juliana Juliana; Suci Aprilliani Utami; Widia Astuti (The International Journal of Business Review (The Jobs Review), 2022)
To gain knowledge and analyze the factors that influence the disclosure of Islamic Social Reporting. And to find out the comparison of the breadth and informativeness of annual reports from manufacturing companies listed on the Jakarta Islamic Index and Bursa Malaysia. This research design uses a causality description technique with a quantitative approach. This study used a purposive sampling technique to determine the sample used in this study. The data analysis technique used in this research is panel data regression analysis technique using an analytical tool in the form of the Eviews version 10. The results show that the level of liquidity, leverage and company age have a positive and significant effect, while the level of profitability and the size of the board of commissioners do not. significant effect on the disclosure of Islamic Social Reporting. Based on each variable, it shows that the Jakarta Islamic Index is superior to the level of disclosure of Islamic Social Reporting, the level of profitability, and the level of leverage. Meanwhile, Bursa Malaysia only excels in terms of liquidity. For the size of the board of commissioners and the age level of the company, both the Jakarta Islamic Index and Bursa Malaysia yield the same results, which have met the standards of their respective provisions. The application of the disclosure of the Islamic Social Reporting Index in the annual reports published by manufacturing companies becomes more extensive, informative and pays attention to sharia compliance as a form of responsibility to Allah SWT and humans. This research is a direct study of the influence of the factors that influence the disclosure of Islamic Social Reporting, as well as comparing the two countries. These results show that the Jakarta Islamic Index is better and informative regarding the content of annual report publications based on the Islamic Social Reporting Index compared to Bursa Malaysia.